Dynamic Commercialization Strategies for Disruptive Technologies: Evidence from the Speech Recognition Industry - Marx, Matt; Gans, Joshua S.; Hsu, David H. (Management Science, 2014)
When start-up innovation involves a potentially disruptive technology—initially lagging in the predominant performance metric, but with a potentially favorable trajectory of improvement—incumbents may be wary of engaging in cooperative commercialization with the start-up. While the prevailing theory of disruptive innovation suggests that this will lead to (exclusively) competitive commercialization and the eventual replacement of incumbents, we consider a dynamic strategy involving product market entry before switching to a cooperative commercialization strategy. Empirical evidence from the automated speech recognition industry from 1952 to 2010 confirms our main hypothesis. This paper was accepted by Bruno Cassiman, business strategy.